THE IMPACT OF PEDAGOGIC, PERSONALITY, PROFESSIONAL, AND SOCIAL COMPETENCE ON TEACHER PERFORMANCE: A QUANTITATIVE STUDY - Dudung Zulkipli; Ellin Herlina; Weti Kurniawati (International Journal of Management, Economic, Business and Accounting, 2022)
Purpose of the study —This study aims to determine: How big is the influence of Pedagogic Competence, Personality Competence, Professional Competence and Social Competence on Teacher Performance at SMK Negeri 1 Cirebon, Cirebon City, either partially or simultaneouslyResearch method—Design This study uses a quantitative approach. Quantitative approach, survey method, this type of research is causal associative research with data analysis technique using Multiple Linear Regression analysisResult— The results of this study indicate: 1) There is a partial influence of pedagogic competence on teacher performance at SMK Negeri 1 Cirebon, Cirebon City. The magnitude of the positive influence of pedagogic competence on teacher performance is 17%. 2) There is a partial influence of personality competence on teacher performance at SMK Negeri 1 Cirebon, Cirebon City. The magnitude of the influence of Personality Competence on Teacher Performance is 43%. 3) There is a partial effect of professional competence on teacher performance at SMK Negeri 1 Cirebon, Cirebon City. The magnitude of the influence of Professional Competence on Teacher Performance is 62%. 4) There is a partial effect of social competence on teacher performance at SMK Negeri 1 Cirebon, Cirebon City. The magnitude of the influence The magnitude of the influence of Social Competence on Teacher Performance is 92.2%. 5) There is a simultaneous influence of Pedagogic Competence, Personality Competence, Professional Competence and Social Co petence on Teacher Performance at SMK Negeri 1 Cirebon, Cirebon City. The magnitude of the influence of Pedagogic Competence, Personality Competence, Professional Competence, Social Competence simultaneously on Teacher Performance on Performance is 99.5%Conclusion— the study aimed to determine the influence of Pedagogic Competence, Personality Competence, Professional Competence, and Social Competence on teacher performance at SMK Negeri 1 Cirebon, Cirebon City. The research was conducted at SMK Negeri 1 Cirebon, Cirebon City and surveyed a sample of 60 teachers out of a population of 105 teachers. The research design used a quantitative approach, survey method, and causal associative research, with data analyzed using multiple linear regression analysis. The results of the study indicate that there is a partial influence of pedagogic competence, personality competence, professional competence, and social competence on teacher performance at SMK Negeri 1 Cirebon, Cirebon City. The magnitude of the influence of each competency on teacher performance is 17% for pedagogic competence, 43% for personality competence, 62% for professional competence, and 92.2% for social competence. Additionally, the study found that there is a simultaneous influence of all four ompetencies on teacher performance at SMK Negeri 1 Cirebon, Cirebon City, with a magnitude of 99.5%. This research shows that all four competencies play an important role in teacher performance and should be considered in teacher development and evaluation at SMK Negeri 1 Cirebon, Cirebon City.